2000
DOI: 10.1046/j.1440-1746.2000.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin‐resistance and point mutations in the 23S rRNA gene in Helicobacter pylori isolates from Japan

Abstract: The results suggest that the point mutation in the 23S rRNA gene is commonly seen in clarithromycin-resistant H. pylori and it contributes to the treatment failure in Japan. The PCR-RFLP system is a sensitive method by which to diagnose H. pylori infection as well as a simple method for detecting clarithromycin resistance without bacterial culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
3
23
1
2
Order By: Relevance
“…Resistance to clarithromycin observed before the year 2000 in this study is probably due to the use of the antimicrobial agent for other infections. The reported prevalence of H. pylori resistance to clarithromycin in Japan is reported at 6-21% [11,13,16,24,25]. The reported prevalence in western countries is from 1 to 17% [9,10,15,19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to clarithromycin observed before the year 2000 in this study is probably due to the use of the antimicrobial agent for other infections. The reported prevalence of H. pylori resistance to clarithromycin in Japan is reported at 6-21% [11,13,16,24,25]. The reported prevalence in western countries is from 1 to 17% [9,10,15,19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal DNA of the isolates was extracted by the cetyltrimethylammonium bromide method. A 1,300-bp fragment of the 23S rRNA (bp 1627 to 2926; GenBank accession number U27270) was amplified with primers Cla1 (5Ј-G GCTCTTTGAGTCCTTTTAGGAC-3Ј) and Cla4 (5Ј GCAT TACTGCGCTCACACAT-3Ј) as described previously (21). The PCR product was purified with a Microcon centrifugal filter device (Millipore Corporation, Bedford, Mass.…”
Section: Eradication Ofmentioning
confidence: 99%
“…30) Some reports have associated A2143G mutation with higher MIC (Ͼ25 mg/l) to clarithromycin than A2144G mutation and that the frequency of later mutation is higher than former. 31) Contrarily, a recent report by Rimbara et al, suggested that not all A2143G mutations render high resistance to clarithromycin. 32) Infact, all nine CR strains analyzed in our study revealed the A2144G mutation in 23s rRNA gene, however MIC's of the all the strains had a wide variation (MIC: 8-Ͼ256 mg/l).…”
Section: Discussionmentioning
confidence: 99%